Eosinophilic oesophagitis (in nickel-allergic patient) regressed after nickel oral desensitization: A case report. (February 2019) - Nucera, Eleonora; Chini, Raffaella; Rizzi, Angela; Schiavino, Domenico; Buonomo, Alessandro; Aruanno, Arianna; Ricci, Riccardo; Mangiola, Francesca; Campanale, Maria Chiara; Gasbarrini, Antonio; Petruzziello, Lucio
The eosinophilic oesophagitis (EoE) is a chronic immune/antigen disorder of the oesophagus clinically characterized by dysphagia and pathologically by mucosa eosinophilic infiltration. Th2-type allergic reactions are considered having important roles in the aetiopathogenesis of EoE. Avoidance of food allergens, administration of steroidal anti-inflammatory medications and dilation of the oesophagus are the most important treatments. 'Systemic nickel allergy syndrome' (SNAS) interests about 20% of patients with nickel contact allergy which could present systemic cutaneous manifestations (urticaria, oedema, etc.) and also respiratory and digestive symptoms (meteorism, abdominal pain, diarrhoea, etc.). In the literature, it is demonstrated that nickel oral immunotherapy is effective in reducing symptoms of SNAS and in modulating inflammatory parameters. We describe the case of a 48-year-old woman suffering from EoE not responsive to the topical steroid administration and diagnosis of SNAS. The patient started nickel oral desensitization according to the literature protocol continuing nickel-free diet. After 1 year from the beginning of the treatment, during the maintenance dose (500 ng three times a week), she decreased gradually the dosage of immunotherapy and reintroduced all the culprit foods. After the immunotherapy interruption, during the free diet, she repeated the oesophagogastroscopy with a complete macroscopic and histological resolution. We showed the first case of an EoE in a patient affected by SNAS responsive to the nickel-free diet and the oral immunotherapy.